Dietetic research of infant nutrition and protein efficiency ratio for some infant formulas from Croatian market - Vesna Zechner Krpan; Nikolina Mrduljaš; Martina Sučić; Mirjana Hruškar; Ksenija Marković; Ines Panjkota Krbavčić; Irena Colić Barić (Mljekarstvo)
The aim of this research was to establish the state of infant nutrition mode in Croatia, with special regard to nutrition quality parameter protein efficiency ratio (PER) of the most used infant formulas. Methods included dietetic survey (n=255 mothers of infants) in urban area and PER (protein efficiency ratio) determination in vivo by rats and infants for the most used infant formulas in Croatian market. Results of dietetic survey showed that almost half of examinees (49.4 %) claim that their infants are exclusively breastfed. Significant amount of examinees (33.3 %) used mixed breast-and-formula feed for their infants. There are also 17.3 % mothers whose infants are exclusively formula fed. According to PER values in infants, Samples 1-4 had very similar quality (PER 2.01-2.36). PER values in rats varied from 1.34 to 3.36. In spite of different PER values for infants and rats, these differences are not statistically significant (p<0.05), therefore it can be presumed that both methods can be used equally.